Pandemic and crisis discourse communicating COVID-19 and public health strategy - Musolff, Andreas 1957-; Breeze, Ruth; Kondo, Kayo; Vilar-Lluch, Sara (Bloomsbury Academic, 2022)
"The COVID-19 pandemic has led to a host of critical reflections about discourse practises dealing with public health issues. Situating crisis communication at the centre of societal and political debates about responses to the pandemic, this volume analyses the discursive strategies used in a variety of settings. Exploring how crisis discourse has become a part of managing the public health crisis itself, this book focuses on the communicative tasks and challenges for both speakers and their public audiences in seven areas: - establishment of discursive and political authority - official governmental and expert communication to the public - public understanding of government communication - legitimation of public health management as a 'war' - judging and blaming a collective other - cross-national comparison and rivalry - empathy and encouragement Covering global discourses from Asia, Europe, the Middle East, North and South America, and New Zealand, chapters use corpus-based data to cast light on these issues from a variety of languages. With crisis discourse already the object of fierce national and international debates about the appropriateness of specific communicative styles, information management and 'verbal hygiene', Pandemic and Crisis Discourse offers an authoritative intervention from language experts."
Primäre Informationsquelle Landing Page (Bloomsbury Collections), da kein Titelblatt vorhanden
Keywords: Politik; Öffentlichkeitsarbeit; Kommunikation; COVID-19; Krisenmanagement; Soziolinguistik; Sozialhygiene; COVID-19 (Disease); COVID-19 (Disease) / Political aspects; Public health; Public relations; Crisis management; Semantics, discourse analysis, etc,Computational linguistics,Sociolinguistics; Aufsatzsammlung